Fluxos de biomassa e padrões de desfolha em pastagem de papuã submetida a adubação nitrogenada - Hundertmarck, Anelise Pereira (2015)
The leaf biomass flows of Alexandergrass (Urochloa plantaginea (Link) Hitch), the intensity and frequency of defoliation were evaluated using Zero, 100, 200 or 300 kg ha-1 of nitrogen (N), in the form of urea. The grazing method was continuous with variable number of animals to keep the forage mass in 3000 kg ha-1 DM. The experimental animals were Angus heifers with age and initial average body weight of 15 months and 241.5±5.7 kg, respectively. The experimental design was completely randomized following a repeated measure arrangement measures with four treatments and variable number of experimental units. Application of 100 kg ha-1 N provided higher leaf blades growth flow. The senescence and intake fluxes and defoliation intensity were similar in N fertilizer rates used. The return frequency (days) was influenced by N rates and evaluation periods. It is recommended using 100 kg ha-1 N in Alexandergrass pasture.